THE INFLUENCE OF DIGITALIZATION ON FAMILY COMMUNICATION: LITERATURE ANALYSIS ON FAMILY INTERACTION IN THE DIGITAL ERA - Muhammad Ni’amul Hanif; Caroline Caroline; Budiawan (RADJA PUBLIKA, 2025)
This study explores the influence of digitalization on family communication by analyzing literature that discusses family interactions in the digital age. The findings show that digital technology facilitates communication across distances and time, enabling family members to stay connected despite being physically distant and increasing parents' involvement in their children's lives. However, the findings also reveal the negative impacts of over-reliance on digital devices, including a decline in the quality of face-to-face interactions and potential risks such as exposure to inappropriate content and cyberbullying. In conclusion, although digitalization offers various benefits for family communication, the wise management of technology use is necessary to balance the benefits of digital communication with maintaining interpersonal closeness and strong emotional relationships.